Relation between Vitamin B12 Levels and Smell Affection in COVID-19 Patients - Elsayad, Osama A.; Abdou, Said Mohammed (International Archives of Otorhinolaryngology, 2022)
Introduction Olfactory and gustative alterations are frequent in the initial stages of the COVID-19 infection. Vitamin B12 deficiency has been linked to olfactory dysfunction.Objective The present study aimed to assess the relationship between vitamin B12 levels and smell affection in COVID-19 patients.Methods The present study included 201 laboratory-confirmed COVID-19 patients. Smell affection was assessed using self-rated olfactory function. Serum vitamin B12 levels were assessed using commercial enzyme-linked immunosorbent assay (ELISA) kits.Results According to the smell function assessment, the patients were classified into three categories: normal osmesis (n = 77), hyposmia (n = 49), and anosmia (n = 75) (Fig. 1). Four weeks later, 195 patients (97.0%) had their normal smell function restored. The remainder 6 patients included 4 anosmic and 2 hyposmic patients. Patients with hyposmia or anosmia had significantly lower vitamin B12 levels when compared with patients with normal osmesis (median [IQR]: 363.0 [198.0–539.0] versus 337.0 [175.0–467.0] and 491.0 [364.5–584.5] pg/ml, respectively, p < 0.001).Conclusion Vitamin B12 appears to have some contribution to smell affection in patients with COVID-19 infection.
Keywords: COVID-19; vitamin B12; olfactory dysfunction